2-(3-(chloromethyl)benzoyloxy)benzoic Acid Increases CD4+ Regulatory T-Cell Population and FoxP3 Expression in Lipopolysaccharide-induced Mice - Yudy Tjahjono; Caroline Caroline; Jusak Nugraha; Kuncoro Foe; Srikanth Karnati; Süleyman Ergün; Nico Jafet; Oryza Chrisantia; I Made Andika Bara Kusuma; Hendy Wijaya; Wuryanto Hadinugroho; Dwi Aris Agung Nugrahaningsih; Dwi Liliek Kusindarta; Yufita Ratnasari Wilianto; Senny Yesery Esar; Hevi Wihadmadyatami (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Lipopolysaccharide (LPS) has been reported to increase CD4+ regulatory T-cell (CD4+ Treg) populations. Acetylsalicylic acid (ASA) has been reported to have immunomodulatory activity, but it may induce chronic gastric ulceration. Another salicylic acid-bearing compound, 2-(3-(chloromethyl)benzoyloxy)benzoic acid (3-CH2Cl), has been reported to have less gastric mucosal damage. However, the effect of 3-CH2Cl on CD4+ Tregs in LPS-induced mice is still unknown. Therefore, the present study was conducted to investigate the immunomodulatory effect of 3-CH2Cl on CD4+ T-cell and CD4+ Treg populations as well as FoxP3 expression in LPS-induced mice.METHODS: Synthesis of 3-CH2Cl was performed by mixing salicylic acid and chloromethylbenzoylchloride with the catalyzation of pyridine, acetone and heat. The 3-CH2Cl tablets were prepared using direct compression method. After intraperitoneal injection of 1 mg/kg BW LPS to mice, 60 mg/kg BW ASA or 60 mg/kg BW 3-CH2Cl was given orally for 3 days. The splenocyte was obtained through splenectomy and collagenase digestion. The population of CD4+ T-cells and CD4+ Tregs, as well as the splenic FoxP3 expression were determined using flow cytometry technique.RESULTS: CD4+ T-cell populations in mice treated with LPS and 3-CH2Cl or ASA were lower than those treated with LPS merely. Meanwhile, CD4+ Treg populations and FoxP3 expression levels in mice treated with LPS and 3-CH2Cl or ASA were higher than those treated with LPS merely.CONCLUSION: Since 3-CH2Cl could decrease CD4+ T-cell population and increase CD4+ Treg population mediated by the increase of FoxP3 expression in LPS-induced inflammation, it may act as a potential therapeutic drug to reduce inflammatory conditions.KEYWORDS: 2-(3-(chloromethyl)benzoyloxy)benzoic acid, acetylsalicylic acid, CD4, T-regulatory cells, FoxP3, LPS